2018
DOI: 10.9734/jpri/2018/41936
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Tolerance Effects on Neurotransmitters and Related Receptors: Definition, Overview and Update

Abstract: Morphine is the essential opioid drug that use in the clinic to attenuate chronic and severe pain. However long-term administration of morphine leads to the development of anti-nociceptive morphine tolerance. Mechanisms that involved in morphine tolerance are complicated and affect a different part of CNS and change neural circuits. One of the most critical candidates for the development of morphine tolerance are neurotransmitters Which makes the communication between neurons and establish neural circuits. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Fifty male Wistar rats (200-250 g) were used in this study. Each animal was housed in one cage and had free access to food and water [24] . Rats were randomly divided into five groups (n = 10 per group): (1) control group, without any intervention and injection; (2) sham group, with PBS intrahippocampal injection without any dietary plan; (3) Alzheimer group, with Aβ1-40 intrahippocampal injection without any dietary plan; (4) Alzheimer-probiotics (A + P) group, with Aβ1-40 intrahippocampal injection and receiving 2 g (10 10 CFU) probiotics (Lactobacillus reuteri, Lactobacillus rhamnosus, and Bifidobacterium infantis) orally once a day for 10 weeks; (5) AD + rivastigmine group, receiving rivastigmine (0.6 mg/kg) orally once a day for two weeks.…”
Section: Animalsmentioning
confidence: 99%
“…Fifty male Wistar rats (200-250 g) were used in this study. Each animal was housed in one cage and had free access to food and water [24] . Rats were randomly divided into five groups (n = 10 per group): (1) control group, without any intervention and injection; (2) sham group, with PBS intrahippocampal injection without any dietary plan; (3) Alzheimer group, with Aβ1-40 intrahippocampal injection without any dietary plan; (4) Alzheimer-probiotics (A + P) group, with Aβ1-40 intrahippocampal injection and receiving 2 g (10 10 CFU) probiotics (Lactobacillus reuteri, Lactobacillus rhamnosus, and Bifidobacterium infantis) orally once a day for 10 weeks; (5) AD + rivastigmine group, receiving rivastigmine (0.6 mg/kg) orally once a day for two weeks.…”
Section: Animalsmentioning
confidence: 99%
“…[30]. The human body works like a perfect machine, and the introduction of a foreign object like alcohol causes the harmony of the machinery to bend out of place and throw everything out of balance [31].The article gives as to how our brain acts in the presence of alcohol, not even for a long time but short as well, and is helpful to find a corrective methodic treatment for alcoholism [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are the most common analgesic drugs applied in clinical practice to treat chronic pain [ 1 ] . As a MOR agonist, morphine is used extensively to attenuate chronic pain, but morphine tolerance, dependence, and addiction restrict its administration [ 2 , 3 ] . Nowadays, co-administration of morphine plus other drugs suggests diminishing this tolerance [ 4 - 6 ] .…”
Section: Introductionmentioning
confidence: 99%
“…As a GABA B agonist, baclofen might be beneficial to minimize morphine tolerance [ 7 , 8 ] . Recently, behavioral and molecular studies have shown that baclofen could be used along with opioid drugs to delay tolerance and dependence to opioids [ 3 , 9 ] . Evidence has also indicated that baclofen may potentiate morphine analgesia in chronic use of opioids and can reduce many adverse effect of chronic administration of opioids [ 6 , 10 ] .…”
Section: Introductionmentioning
confidence: 99%